ANTHROPOMETRIC INDICATORS OF 14-16 YEAR OLD CHILDREN REGULARLY ENGAGED IN ATHLETICS AND THEIR ANALYSIS - Turgunboyeva , Komilaxon (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the importance of anthropometric indicators in the physical development of adolescents aged 14–16, especially the body composition characteristics of athletes regularly involved in athletics. The level of physical development of adolescent athletes is assessed based on indicators such as height, body weight, chest circumference, and body mass index.